1991
DOI: 10.1016/0014-5793(91)80510-a
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphorylation in isolated nuclei from etiolated Avena seedlings Effects of red/far‐red light and cholera toxin

Abstract: We have studied the phosphorylation/dephosphorylation of several nuclear proteins in isolated nuclei from etiolated Avena seedlings as a function of red/far-red light. The effect of stimulatory (ADP-ribosylation by cholera toxin) or inhibitory (GDP beta S) conditions for GTP-binding proteins was also studied. Red or far-red light enhanced the phosphorylation level of 2 nuclear proteins with molecular masses of 75 and 60 kDa. The phosphorylation pattern was affected by the addition of cholera toxin or GDP beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…There have been several reports suggesting that the phosphorylation0dephosphorylation of a number of proteins is mediated by the phytochrome phototransformation~Gallagher et Otto & Schäfer, 1988;Park & Chae, 1989;Romero et al, 1991;Doshi et al, 1992!. For example, phytochrome samples from irradiated seedlings have a higher phosphate content as compared to the samples from nonirradiated tissue~Lapko et al, 1996!.…”
Section: Posttranslational Modifications In Oat Phyamentioning
confidence: 99%
“…There have been several reports suggesting that the phosphorylation0dephosphorylation of a number of proteins is mediated by the phytochrome phototransformation~Gallagher et Otto & Schäfer, 1988;Park & Chae, 1989;Romero et al, 1991;Doshi et al, 1992!. For example, phytochrome samples from irradiated seedlings have a higher phosphate content as compared to the samples from nonirradiated tissue~Lapko et al, 1996!.…”
Section: Posttranslational Modifications In Oat Phyamentioning
confidence: 99%
“…Since the visual transduction cascade in rod photoreceptor cells represents a classical model system for GPCR signaling [13], this well-understood signaling pathway has promoted researchers to investigate a similar role of G-proteins in the light sensing of plants. The early experiments to test this hypothesis were conducted with two adenosine diphos-npg phate (ADP)-ribosylating drugs, namely, the cholera toxin that constitutively activates the G-protein pathway and the pertussis toxin that switches off the G-protein signaling pathway [14][15][16][17]. Similarly, two chemical agents, GTPγs (a Gα-subunit activator) and GDPβs (a Gα-subunit inhibitor), have also been used in the study of the G-protein signaling pathway [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In etiolated pea seedlings, G-protein associated with plasma membranes was involved in blue-light signal transduction (Warpeha et al, 1991). The effect of red and far-red light on G-protein in oat seedlings was investigated by Romero et al (1991). They showed that the expression of phytochromeregulated genes, cab and phy, was affected by cholera toxin, an inhibitor of G-protein.…”
Section: Introductionmentioning
confidence: 99%